A high-resolution wave energy resource assessment of Indonesia. (November 2020) - Ribal, Agustinus; Babanin, Alexander V.; Zieger, Stefan; Liu, Qingxiang
Abstract: Indonesia is an archipelago country with great potential for marine renewable energy, particularly for wave energy. This study will provide a wave energy assessment of Indonesia over a 6.5-year period (2011–2017) with resolution about 5.5 km. This assessment is based on data generated with a two-way nested high-resolution wave model WAVEWATCH III with observation-based physics (ST6). Three grids have been generated, namely a 'high resolution' of 3 arc-minute (0.05°) grid is nested inside a 12 arc-minute (0.2°) grid which is nested within a 0.5° global grid. Validations against altimeters and buoys show good agreement with the model. Mean wave energy has been classified based on meteorological seasons and it is found that the most energetic months are June, July, August for all areas of south, southwest and west of Indonesia where it can exceed 30 kW/m. In some locations wave energy is available throughout the entire year, that is in the south of Jawa island, Bali island and West Nusa Tenggara while in the region of west Sumatera, promising wave energy is available during the time from March to November. In addition, within the Indonesian Archipelago the monthly variations are about 5 kW/m and relatively small in terms of absolute values but this region is large relative to the mean wave power energy. Highlights: Wave energy assessment for Indonesian archipelago with spatial resolution of 0.05°. Based on a dynamically downscaled wave model with observation-based physics (ST6). Mean wave power in excess of 30 kW/m was found for season June to August. 10% of mean wave power exceeds 40 kW/m with the top-one percent up to 60 kW/m.